In‐vivo comparison of the Ni‐free steel X13CrMnMoN18–14‐3 and titanium alloy implants in rabbit femora – A promising steel for orthopedic surgery. Issue 6 (9th November 2020) - Kauther, Max Daniel; Gödde, Kai; Burggraf, Manuel; Hilken, Gero; Wissmann, Andreas; Krüger, Christine; Lask, Sara; Jung, Ole; Mitevski, Bojan; Fischer, Alfons; Dudda, Marcel; Behr, Björn; et al.
Abstract: A variety of metallic biomaterials is used for fracture fixation. Allergic reactions towards nickel‐containing steels urge the need for alternatives. The present study investigated the suitability of the nickel‐free stainless steel P2000 in comparison to titanium alloy implants for bone surgical applications in a rabbit femora defect model. Thirty‐six rabbits received two different cylindrical implants press‐fit inserted into the distal femoral metaphysis. At day 0, 28, and 56, implant ingrowth was monitored by radiography; implant stability was assessed by pull‐out torque measurements while bone‐to‐implant contact (BIC) was determined histomorphometrically. Radiography revealed comparable implant ingrowth after 1 and 2 months for both implant materials. The pull‐out force of P2000 tended to be higher than that for titanium at day 28 ( p = .076) but the values were comparable at day 56 ( p = .905). At day 56, implant fixation was significantly increased compared to the day of surgery for both, P2000 ( p = .030) and for titanium alloy ( p = .026). Microscopic examination revealed that both implant types appeared to be well integrated and firmly anchored in the bone. BIC ratio of titanium alloy tended to be higher at day 28 ( p = .079) but they did not differ significantly at day 56 ( p = .711). In the present rabbit femora defect model, the nickel‐free stainless steel P2000 provides primary stability and osseointegration comparable to that of titanium alloy implants.